توزع مستويات فان هيلي (Van Hiele) للتفكير الهندسي عند الطلبة وعلاقته بالبرهان الهندسي والتفكير المنطقي الرياضي (دراسة ميدانية في مدينة اللاذقية) - نصور, رغداء (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aimed to extent of the distribution of the Van Hiele levels in geometrical reasoning in secondary school students (the second secondary grade), and its relationship with geometric- proof And logical-mathematical thinking, And a random sample of (200) two hundred students was chosen from both genders from the public schools in the Lattakia city, The research used the Van Hiele geometry test, and she used Achievement test for writing proofs in Geometry, And logical-mathematical thinking test. The results showed the Van Hiele levels of geometrical reasoning were present distributed at the first fourth levels with varying degrees in secondary school students (the second secondary grade), and There was a strong correlation between the two variables (Van Hiele / Geometric proof) for students, and There is a strong and positive relationship between the two variables(Logical-mathematical thinking / Geometry proof) for students, and There was a strong correlation between the two variables (Logical-mathematical thinking / Van Hiele) for students. هدفت هذه الدراسة إلى تحديد توزع مستويات فان هيلي للتفكير الهندسي عند الطلبة وعلاقته بالبرهان الهندسي والتفكير المنطقي الرياضي, وتكونت عينة البحث من(200) طالباً وطالبة مـن الصف الثاني الثانوي من المدارس الحكومية في مدينة اللاذقية, واستخدمت الباحثة اختبار فان هيلي للتفكير الهندسي, وأعدت اختباراً تحصيلياً في كتابة البرهان الهندسي, واختبار التفكير المنطقي الرياضي.أظهرت نتائج الدراسة أن مستويات فان هيلي للتفكير الهندسي تتوزع على المستويات الأربعة الأولى عند طلبة الصف الثاني الثانوي, وتوجد علاقة ارتباط طردية وقوية بين المتغيرين فان هيلي (Van Hiele)والبرهان الهندسي بالنسبة للطلبة, وتوصلت الدراسة إلى وجود علاقة ارتباط طردية وقوية بين درجات الطلبة على اختبار التفكير المنطقي الرياضي ودرجاتهم على اختبار البرهان الهندسي, وبينت الدراسة إلى أنه كلما ازدادت درجات الطلبة في اختبار فان هيلي(Van Hiele) ازدادت درجاتهم في التفكير المنطقي الرياضي, وهذا يشير إلى وجود علاقة طردية وقوية بين درجات الطلبة على اختباري فان هيلي (Van Hiele) للتفكير الهندسي والتفكير المنطقي الرياضي,